Hasil belajar evaluasi program ditinjau dari kreativitas dan motivasi berprestasi pada mahasiswa S2 PEP PPs Universitas Negeri Makassar - Triyanto Pristiwaluyo; Muhammad Sidin Ali; Baso Intang Sappaile (Seminar Nasional LP2M UNM, 2019)
This research is a survey research focused on learning outcomes of program evaluation. The purpose of the study was to find out: 1) the relationship between creativity and achievement motivation with program evaluation learning outcomes, both together and partially. The population of the study were S-2 students of PEP PPs UNM. Sampling is used random class with the assumption that all classes are relatively homogeneous. Data is processed by inferential analysis. The conclusions obtained are 1) there is a positive relationship between creativity and learning evaluation program results, 2) there is a positive relationship between achievement motivation and learning evaluation program results, 3) there is a positive relationship between creativity and achievement motivation together with learning outcomes program evaluation, 4) there is a positive relationship between creativity and program evaluation learning outcomes if achievement motivation is controlled, and 5) there is a significant positive relationship between achievement motivation and program evaluation learning outcomes if creativity is controlled, S-2 PEP PPs UNM students.